PENGARUH LINGKUNGAN KELUARGA DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR MELALUI MOTIVASI BELAJAR - Dewi Sartika Rahayu; Novi Trisnawati (Program Studi PGSD Universitas Flores, 2021)
The purpose of this study was to determine the effect of the family environment and learning facilities at school on learning outcomes through learning motivation as an intervening variable at SMKN 10 Surabaya This type of causal associative research with a quantitative approach. Sampling using random sampling technique. Collecting data through observation techniques, interviews, questionnaires and documentation. The results of the study are: 1) there is no significant effect of the family environment on learning outcomes; 2) there is no significant effect of learning facilities on learning outcomes; 3) there is a significant effect of learning motivation on learning outcomes; 4) there is a significant influence of the family environment on learning motivation 5) there is no significant effect of learning facilities on learning motivation; 6) there is a significant influence of the family environment through learning motivation on learning outcomes; 7) there is no significant effect of learning facilities through learning motivation on learning outcomes.